‘The War Never Ends’: Films about the Vietnam War - Scarlette Nhi Do (Limina: A Journal of Historical and Cultural Studies, 2020)
'"The War Never Ends": Films about the Vietnam War' presents an engaging overview of the representations of Vietnamese identity in a broad range of films depicting the Vietnam War, and the complex entanglements of these films with the legacy of the War itself, considering its intersections with racism, nationalism, and selfhood.